The NE Atlantic region: A reappraisal of crustal structure, tectonostratigraphy and magmatic evolution - An introduction to the NAG-TEC project - Péron-Pinvidic, Gwenn; Hopper, John R.; Stoker, Martyn; Gaina, Carmen; Funck, Thomas; Árting, Uni Egholm; Doornenbal, Johannes Cornelis (Geological Society, London, Special Publications, 2018)
The NE Atlantic region and its continental margins (Fig. 1) hold unique information for understanding many aspects of Earth science, from global geodynamics to palaeoceanography and global environmental change. It also holds some of the world's most important hydrocarbon reserves from the North Sea, along the Atlantic margins of Ireland, Britain and Norway, and into the Arctic in the Barents Sea. Historically, studies in the NE Atlantic were important for establishing many of the key ideas during the early part of the plate tectonic revolution. Linear magnetic anomalies along the Reykjanes Ridge were identified as early as in the 1960s (Heirtzler et al. 1966) and provided strong evidence for the seafloor spreading hypothesis (Dietz 1961), which by then had been established as a new and holistic theory (Ewing & Heezen 1956). At the same time, Iceland was already recognized as an intriguing anomalous entity (Böðvarsson & Walker 1964) and contributed to knowledge about how Earth's magnetic field reversed its polarity through time. The fact that rifting occurs in close association with old sutures and orogenic belts led Wilson to propose that the Atlantic Ocean closed and opened again, establishing the concept of the ‘Wilson tectonic cycle’ (Wilson 1966; Dewey 1969). The North Atlantic continental margins have long been considered as archetypal, and divergent margins world-wide are commonly described as ‘Atlantic-type passive margins’. However, it is now accepted that these so-called ‘passive’ margins remain dynamic long after break-up, including post-rift vertical movements of up to kilometre scale. The type examples for such epeirogenic movements being, once again, the North Atlantic margins (Praeg et al. 2005).